PERAN GURU DALAM PENANAMAN KARAKTER KEMANDIRIAN PADA ANAK USIA DINI DI PAUD WAFDAA KIDS CENTER - Sindhi, Ike Kumala; Rosidi, Ayep; Matori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teachers play an important role in instilling the character of independence in early childhood as the basis for independent and responsible development. This study examines the role of teachers in PAUD Wafdaa Kids Center and its supporting and inhibiting factors. The study uses a descriptive qualitative approach to deeply understand the role of teachers in instilling early childhood independence in PAUD Wafdaa Kids Center. Subjects include managers, educators, and early childhood at the site. Data were collected through in-depth interviews and participatory observations; analyzed with an interactive model (reduction, presentation, conclusion). The results of the study show that teachers play the role of facilitators, motivators, guides, and role models through habituation, educational games, and practical life according to children's development at PAUD Wafdaa Kids Center. The main supporting factors for instilling independence are a conducive learning environment, the support of the principal in co-curricular activities, and the active participation of parents. Meanwhile, the inhibiting factors are overprotective parenting, excessive consumption of gadgets, and limitations from teachers.